Efficient routing algorithms for group multicast communication - Wang, Ning. (2008)
The objectives of the research include propose efficient heuristics for group multicast routing problem; derive a tight lower bound of total tree cost to evaluate the performance of proposed heuristics and increase the success rate of building multicast trees for each of the multicast group members.